PENGARUH KOLESTROL TERHADAP KESEHATAN REMAJA : Studi Literatur - Puspitasari, Wulan (Jurnal Kesehatan, 2024)
This study aims to investigate the effect of cholesterol on health and the risk of cardiovascular disease. Cholesterol, a type of fat found in the body and food, plays an important role in the body's normal function. However, high cholesterol levels in the blood can increase the risk of heart and blood vessel disease, such as coronary heart disease and stroke. In this study, data was analyzed from a number of trusted sources to present a comprehensive picture of the influence of cholesterol on health. The results showed that high cholesterol in the blood contributes to the development of heart and blood vessel disease, as well as increasing the risk of heart attack, stroke and peripheral vascular disease. To keep cholesterol in a healthy range, steps such as eating healthy, exercising regularly, avoiding smoking, managing weight, and reducing excessive alcohol consumption are recommended. By paying attention to and managing cholesterol levels well, individuals can reduce the risk of diseases related to high cholesterol and improve overall health..